Foliar carbon and nitrogen concentrations and natural abundance isotope signatures for Larix cajanderi across a tree density gradient in northeastern Siberia, 2017 - Hewitt, Rebecca; Alexander, Heather; Izbicki, Brian; Mack, Michelle (NSF Arctic Data Center, 2018)
As climate warms, tree density at the taiga-tundra ecotone is expected to increase, which may intensify competition for belowground resources in this nitrogen (N) limited environment. To determine the impacts of increased tree density on N cycling and productivity we examined edaphic properties indicative of soil N availability along with aboveground and belowground tree-level traits and stand characteristics related to carbon (C) and N cycling across a tree density gradient of monodominant larch (Larix cajanderi) at the taiga-tundra ecotone in far northeastern Siberia. In this dataset, we quantified foliar carbon and nitrogen concentrations and natural abundance isotope signatures of Larix cajanderi during the peak and the end of the growing season across a gradient of stand densities. We collected foliage from five trees in 26 sites across a tree density gradient near the Northeast Science Station, Russia in July and September 2017. This data set consists of foliar percent carbon, percent nitrogen, natural abundance carbon-13 and nitrogen-15 signatures from foliage.